The Meaning and Importance of Working Cross-Border: A Local Authority Perspective - O'Reilly, Catriona (Irish Journal of Arts Management and Cultural Policy, 2019)
This paper discusses the meaning and origins of cross-border working, particularly the importance of this work and the relationships which are formed in resourcing and nurturing the arts. It includes the views of artists, senior council officials and community leaders which adds greatly to understanding the practicalities, challenges and potentialities of working in a local context for ensuring a sustainable approach to arts development.